Dorothy must die : stories. Vol. 3 - Paige, Danielle (Novelist) (Paige, Danielle (Novelist). Dorothy must die series., 2017)
This third collection of prequel novellas to the Dorothy Must Die series follows the early members of the Revolutionary Order of the Wicked as they begin to form the group that will recruit Amy Gumm and save Oz.--